Scalable Syntheses of Chirally Pure Mono-protected and Orthogonally Di-protected cis-3,4-Diaminotetrahydrofurans - Weiberth, Franz J.; Bourque, Andre J.; Elenbaas, Steven; Hanna, Reda; Powers, Matthew R.; Siegel, Craig S.; Zhao, Jin (Synthesis, 2017)
Scalable and chromatography-free syntheses of chirally pure and orthogonally protected cis-3,4-diaminotetrahydrofurans prepared from a single starting material, 3,4-epoxytetrahydrofuran, are presented.
Keywords: chiral; linker; cis-diamino; TCI; orthogonal; protecting groups